The buffering role of employee resilience in the Relationship between project conflicts and employee burnout with the mediation of negative emotions - Muhammad Syam Aslam; Shuja Ul Islam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study aims to test the hypothesized moderated mediation process combining project conflicts, negative emotions, employee resilience, and employee burnout. It proposes that negative emotions can be considered as a mediator between the relationship of project conflicts and employee burnout, and this mediation effect is moderated by the level of employee resilience. Data were collected from employees working in project-based organizations. The final number of responses was 389. We used structural equation modelling for model fitness and direct relationships, and PROCESS macro model 4 and 14 were used for mediation and moderated mediation analysis respectively. The main finding is that employee resilience moderates the indirect relationship between project conflict and employee burnout via negative emotions. Project conflict has a positive and significant effect on employee burnout. The results of this study help us understand why the higher management of a project-based organization should consider employee resilience to avoid the negative consequences of project conflicts. Resting on the research gaps identified, this study proposes a unique conflict model that hypothesizes a moderated mediation process.
Keywords: 330; Project conflict; task conflict; relationship conflict; process conflict; status conflict; negative emotions; employee resilience; employee burnout; project-based organizations; Pakistan